2013
DOI: 10.3109/03009742.2012.754937
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemokines and their receptors in blood during treatment with the TNF inhibitor infliximab in patients with rheumatoid arthritis

Abstract: The chemokines CXCL10/IP-10, CCL2/MCP-1, and CCL4/MIP-1β, mainly targeting the T-helper (Th)1 immune response, decreased after treatment with anti-TNF, suggesting a more pronounced effect on Th1 activity than on Th2-mediated response. Several chemokine receptors on blood T cells were elevated in RA patients, suggesting that they may be involved in the recruitment of T lymphocytes from the blood to affected tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
3
15
1
4
Order By: Relevance
“…Similar results were obtained by Eriksson et al [39]. In the present study, we observed a rapid but not statistically significant short-time decrease in MCP-1 levels after a single infliximab infusion.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained by Eriksson et al [39]. In the present study, we observed a rapid but not statistically significant short-time decrease in MCP-1 levels after a single infliximab infusion.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study on IFX-treated RA patients found a greater reduction in the chemokines belonging to the Th1 than to the Th2 axis [28]. Other authors have instead observed that a 6 weeks' treatment increases the IFNγ/IL-4 ratio in IFX responders, but does not seem to affect the Th1/Th2 ratio in nonresponder patients [29].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, higher serum levels of CCL22 in patients with RA compared to healthy controls have been reported previously; however, in that study, the majority of the patients were treated with DMARD and there was no information concerning the disease duration [22]. Various treatments have been shown to affect the levels of chemokines in the circulation [15][16][17][18], which suggests that evaluation of chemokines in untreated patients might be advantageous.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, in another cohort with pre-patients and early RA patients in which blood chemokines were investigated, 39% of the patients were treated with prednisolone [14]. Treatment with biological and non-biological DMARD in RA have been shown to alter the chemokine levels in the blood [15][16][17][18], suggesting a need to evaluate chemokines in a pure group of DMARD-naive ueRA patients.…”
Section: Introductionmentioning
confidence: 99%